Biblioteka Tomci Paluszkowej - Bogusławski, Marcin M. (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
I am interested in two books – Piotr Matywiecki’s Stary gmach and petite poucette by Michel Serres. In that context, I ask about the identity of the library, the ethos of the librarian and the place of libraries in the world of mobile people, separated from the stationary.